Evaluation of trace metals in seawater, sediments, and bivalves of Nellore, southeast coast of India, by using multivariate and ecological tool. (September 2019) - Jha, Dilip Kumar; Ratnam, Krupa; Rajaguru, S.; Dharani, G.; Devi, M. Prashanthi; Kirubagaran, R.
Abstract: Urbanization in recent years has driven us to investigate metal contamination on Nellore coast by collecting seawater, sediment, and bivalve samples monthly at five stations from 2015 to 2017. Non-metric multidimensional scaling and cluster analysis indicated that open sea (OS) samples were markedly different from the samples collected at other stations. Strong factor loadings of Al (0.76), Mn (0.79), and Cd (0.78) showed variability in seawater, while those for Fe (0.76), Ni (0.77), Zn (0.85), and Pb (0.81) showed variability in sediment. The mean values of Fe (346 ppm) and Mn (21 ppm) were high in bivalves compared to the mean values of other metals. A higher contamination factor was observed for Cd at Buckingham Canal, while the lowest was observed for sediment in OS. The order of trace metals in sediments according to risk index was Cd > Pb > Cu > Cr > Zn. The results obtained are essential to establish a reference for better comparison of tropical environments. Highlights: The NMDS and cluster analysis indicated that open sea samples were markedly different from other stations. Strong factor loadings of Al (0.76), Mn (0.79) and Cd (0.78) were illustrated variability in seawater. A higher CF was observed for Cd at BC, while lowest for sediment in OS. The order of potential ecological risk index (RI) of trace metals in sediments was Cd > Pb > Cu > Cr > Zn.